Makna Pesan dalam Presentasi Diri Pemeran Pria Transgender pada Acara Karnaval di Kabupaten Nganjuk, Jawa Timur - Muhammad Diak Udin (Indonesian Journal of Humanities and Social Sciences, 2024)
Transgender is a very sensitive issue these days. However, the facts on the ground are that there is a group of men in Nganjuk who portray themselves as transgender men in a carnival event. This research aims to obtain answers to two main questions: First, What is the background of transgender male actors playing themselves at carnival events in Nganjuk; Second, What is the meaning of the message they will convey. Using descriptive qualitative method and the theoretical approach of Alfred Scutz and Max Webber's social action, the following answers were obtained: First, Because of the motive for choosing a role as a transgender man is motivated by: Wanting to take part in the carnival event in Nganjuk in a different way; Simplicity and cost-effectiveness. Second, the Motive Inorder to carnival participants want to convey a message: Restoring carnival as a medium for people's entertainment; The courage to express in public as long as it does not interfere with existing norms; and Not judging people by their external appearance alone. The two findings of this research reinforce Webber's social action theory, that every action taken is deliberate and has an important meaning for the perpetrator.